Evaluation of formaldehyde in residential indoor air at Taman Seri Bintong Maju, Kangar, Perlis - Saizzah Binti Salim (School of Environmental Engineering University Malaysia Perlis, 2011)
Formaldehyde is one of hazardous pollutant which is frequently detected in the indoor air environment. It has been classified as carcinogenic to humans referring to previous human epidemiology and toxicology studies. To gauge the level of risk of this pollutant in residential indoor air in Perlis, a small suburb located at Taman seri Bintong Maju, Kangar was selected for this purpose. A total of 16 houses were selected and this monitoring was conducted in bedroom and living room of the house. Concurrently, the air monitoring at outdoor environment was also conducted to identify source characteristics. The average formaldehyde concentrations in the residential houses in ranged between 30.6 to 85.8 μ/m³. Likewise, the formaldehyde concentration at outdoor environment at residential areas ranged between 85.8 μ/m³. These result suggested that the source of formaldehyde may come from inside of the houses such as furniture and building materials.